Online Booking Systems To Manage Queue At Road Transport Department - Jiga, Iviana (2016)
Long waiting time has long been subjected as one of the main issues at the public sector service counter. This situation was not time justification and may trigger citizen to charge bad perceptions on the service provided which lead to downgraded reputation of the public sector. Road Transport Department (RTD) is one of the public sectors in Malaysia that has been experiencing the issue of excessive waits at their service counter. There were several alternatives that had been introduced to restrain this problem such as the implementation of e-government service through RTD official portal and providing other units to segregate demand such as commencement of other agencies including UTC and myEG. However, this situation still takes place and become one of the most pressing policy issues affecting RTD. Thus, the purpose of this study is to propose an online system that will aid in managing queue during the service and hence, to optimize the waiting time. There was few methods involved in order to achieve the objectives, including conducting observation, semi-structure interview and time study at RTD Bukit Katil, Melaka, develop the online system by using Adobe Dream Weaver, Adobe Cold Fusion and Oracle SQL Developer software, and verify and validate the system through questionnaire and usability study. The first online system is through online queue number booking system. Through this system, clients are able to book their queue number through online system. Besides that, this system also provides the waiting time duration to the clients so that they are able to present at the counter just in time before their service. The second proposal is by using an online queuing system. This system enables clients to book their appointments with the RTD staff according to the specific time. This system also allows client to come and to be attended on time. Through this system, in hope that the waiting time at the RTD could be optimize, besides improving the customer satisfaction and can be a reference for other government agencies to improve their services.